An anfis converter control approach of grid connected wind/PV/battery system - R. Arulmurugan; Swapna Sandaraju (Institute of Advanced Engineering and Science, 2019)
The major objective of this task is a control technique for power flow management of a network associated hybrid PV-wind-battery based system with multi-input transformer coupled bidirectional DC-DC converter using ANFIS controller is introduced. The proposed system intends to fulfill the demand of load, deal with the power flow from the distinctive sources, injects surplus power into the network and charge the battery from framework as and when required. A transformer coupled boost half-bridge converter is used to tackle power from wind, while bidirectional buck-boost converter is used to outfit control from PV alongside battery charging/releasing control. A single stage full-bridge bidirectional converter is used for ac loads and collaboration with grid. The proposed converter has reduced number of intensity change stages. This enhances the effectiveness and unwavering quality of the framework. In this article Adaptive Neuro Fuzzy interference System (ANFIS) is proposed for better performance of the system. Neural system has many inputs and also has multiple outputs but the fuzzy logic has multiple inputs and single output, so the combination of this two is known as ANFIS which is utilized for nonlinear applications. The proposed paper of simulation results acquired using MATLAB/Simulink demonstrate the execution of the proposed control procedure for power stream the executives under different methods of activity.